Leveraging Blockchain Technology to Enhance Climate Resilience in Agriculture - Husain Saif O.; Mohammed G.; Poornima Ediga (SHS Web of Conferences)
Traditional systems of agricultural data management and security frequently fail to do adequately with increased climate variability and the growing need for sustainable agricultural practices. Data integrity, transparency, and efficiency problems currently debilitate current methods to address climate-induced problems. To address such issues, this research proposes to integrate blockchain technology into agricultural systems. The use of Blockchain proves to be a decentralized and immutable ledger for agricultural transactions, which improves data security, transparency, and efficiency. To this end, the proposed system harnesses blockchain to monitor the crop health, manage the supply chain process, and guarantee accurate data record and analysis. This system has significantly improved the accuracy, cost efficiency, and satisfaction of the user. The findings show that on average, the amount of data integrity errors was reduced by a factor of ten, and the overall costs are lower than the traditional approach and were more efficient to operate. The findings indicate that blockchain technology offers a dependable answer to farming climate durability, surpassing existing information administration standards.